P.B.M.U.M. Persatuan Bahasa Melayu Universiti Malaya: Satu kajian tentang perubahan sikap mahasiswa Melayu di Univeraiti Malaya / Noordin Abdul Razak - Noordin , Abdul Razak (1971)
This Graduation Exercise is an attempt at making a concerted study of The Malay Language Society, University Malaya, one of the many campus organisations which presently is becoming a pressure group in Malaysia The history of the society starting from its inception in 1955 up to the present time (1970/71), reflects the changing course of attitude and action of the Malay Undergra.ds generally, towards involving themselves more actively and positively in nation building. This graduation exercise is divided into the following topical:- 1- History of the growth of The Malay Language Society (PBMUM) 2- PBMUM in the period of its language and literary activities. 3- PBMUM in the period of change and struggle. 4- Factors of change of attitude and action in PBMUM 5- Demonstration and PBMUM 6- Conclusion The study reveals that generally the Malay undergrads as a group, were passive and apathetic, but after having realized the country’s economic educational, political and social problems have become more alerted sensitive and vigorous in both their thinking and action.